Adsorption of Anionic Dye from Equeous Solution by Modified Synthetic Zeolite - Abbas, Ahmed M.; Mohammed, Yousif I.; Himdan, Taki A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The adsorption of Congo red (CR) dye on modified synthetic zeolite 5A , the general name of which is Linde Type A (LTA)which is modified by amino mercepto thiadiazole (AMT) and have been characterized by using fourier transform infrared (FT-IR) , x-ray diffraction (XRD) spectroscopies, atomic force microscopy (AFM) and scanning electron microscope (SEM) analysis.In this work Modified zeolite was utilized as adsorbent to remove (CR) dye from aqueous solution by adsorption. Batch experiments were conducted to study the effects contact time , initial concentration of adsorbate and temperature on dye adsorption. The equilibrium adsorption data were analyzed by using several isotherm models ( Freundlich , Langmuir , temkin , Dubinin-Radushkevitch and Redlich–Peterson )models. The best results were achieved with the Redlich–Peterson isotherm equilibrium model. The equilibrium adsorption capacity (qe) increases with the increase of the initial concentration of dye. The values of qe were found to be decreased with the increase of solution temperatures. The thermodynamic parameters ΔG°, ΔH° and ΔS° have been calculated.